Financial management : Theory & practice - Brigham, Eugene F.; Ehrhardt, Michael C. (Boston Cengage Learning, 2017)
The book begins with a presentation of corporate finance fundamentals before progressing to discussions of specific techniques used to maximize the value of a firm.
Keywords: Tài chính - Ngân hàng.